Rancangan Telegram Bot Sebagai Media Informasi dan Pelayanan Pelanggan - Mida Choerunisa (Jurnal Ilmiah Wahana Pendidikan, 2022)
Perumda Water Drinking Tugu Tirta Malang City is one of the BUMD companies based on information technology and has excellent customer service such as having a special platform to handle customer complaints. Perumda Water Drinking Tugu Tirta Malang City has not been effective enough. The obstacles faced now at Perumda Water Drinking Tugu Tirta Malang City based on interviews with resource persons are that there are no bots to handle customer needs, check bills, check payment locations, check service hours, as well as notifications in case of disturbances and information for customers. To create it in accordance with the vision and mission of Perumda Water Drinking Tugu Tirta Malang City requires professional software and systems. The purpose of this research is to build a telegram bot system as a medium of information and customer service using the PHP program at the Tugu Tirta Water Company Malang and the test results from the PHP implementation to build a telegram bot system at the Tugu Tirta Drinking Water Company Malang. This study will use the waterfall method is a software requirements analysis, design, code generation, testing, maintenance. The results of this study Perumda Water Drinking Tugu Tirta Malang City requires the required software has been adjusted to the needs based on existing problems.